THE EFFECT OF FLUSHING AND SURGING AIR TREATMENT ON THE TURBOCHARGER ON HIGH EXHAUST GAS TEMPERATURE ON MV SHIP. BEAUTIFUL FOOD - Sumali, Bambang; April Gunawan; Adele Apriliu Maharano (Dinasti International Journal of Digital Business Management, 2022)
In supporting the process of monitoring high exhaust gas temperatures on the MV ship. Beautiful Food, still There were several problems with the company and crew related to the treatment of rinse air and high exhaust gas temperatures. The problem is the high level of non-optimal treatment of rinse air and frequent occurrence of surging on the turbocharger on board. Based on these problems, the authors conducted an analysis to determine whether there was an effect of rinse and surging air treatment on the turbocharger on the high exhaust gas temperature. The type of research used is quantitative method. Data was collected by using questionnaires distributed directly to 30 respondents, namely the third machinist who was taking ATT II class at the Jakarta Shipping Science College with a total of 20 statements. In looking for the results of the calculations the author uses the SPSS 25 program and performs several data analyzes, namely: multiple linear regression analysis, correlation test, validity test, determination test, f-test and t-test. Conclusions in this study were carried out by comparing the data obtained from the answers of existing respondents. Based on the acquisition of questionnaire data and data processing. The results showed that the rinse and surging air treatments on the turbocharger together proved to be positive and significant for the high exhaust gas temperature on the MV ship. Beautiful Food with F .value count > F table or 66.633 > 3.3. The author describes several solutions to improve monitoring activities for high temperatures exhaust gases, namely: the company and MV crew. Boga Indah must optimize air treatment rinse well, optimize cooling air temperature in performing rinse air maintenance, improve the cleanliness of the rinse air filter to obtain maximum rinse air quality, provide training to ship crews on proper and proper turbocharger operation can reduce the risk of surging, and the most important thing is to monitor the occurrence of surging on the turbocharger with a good strategy so that there are no obstacles and have a positive influence on the high exhaust gas temperature on the MV ship. Beautiful Food.